Operating room scheduling considering surgeons' preferences and cooperative operations. (July 2021) - Park, Jaesang; Kim, Byung-In; Eom, Myungeun; Choi, Byung Kwan
Highlights: A real-world operating room scheduling problem with 32 rooms is considered. Doctors' preferences and cooperative operations are considered. A mixed integer programming model for the scheduling problem is developed. An efficient heuristic algorithm is proposed for the problem. Abstract: Operating rooms (ORs) are one of the most important facilities in any hospital, and efficient OR scheduling is necessary to optimize hospital profits as well as to provide good healthcare services. In this study, we focus on an OR scheduling problem for a Korean university hospital with 32 ORs, in which the surgeons' preferred rooms and times are considered. Cooperative operation (CO-OP), which is a type of operation in which multiple surgeons cooperatively manage patients, is also considered. Although CO-OP is performed in many large hospitals, there appears to be no accessible literature on this subject. We propose a mathematical programming model and solution approach to solve the scheduling problem. The objective is to minimize both the number of ORs used and the overtime, while providing a satisfactory result based on surgeons' OR preferences. Experimental results on real cases demonstrated the effectiveness of the proposed algorithm in generating better schedules than those manually generated by a hospital manager or mathematically generated using a commercial solver.